RARS2 mutations in a sibship with infantile spasms. (8th April 2016) - Ngoh, Adeline; Bras, Jose; Guerreiro, Rita; Meyer, Esther; McTague, Amy; Dawson, Eleanor; Mankad, Kshitij; Gunny, Roxana; Clayton, Peter; Mills, Philippa B.; Thornton, Rachel; Lai, Ming; et al.
Summary: Pontocerebellar hypoplasia is a group of heterogeneous neurodevelopmental disorders characterized by reduced volume of the brainstem and cerebellum. We report two male siblings who presented with early infantile clonic seizures, and then developed infantile spasms associated with prominent isolated cerebellar hypoplasia/atrophy on magnetic resonance imaging (MRI). Using whole exome sequencing techniques, both were found to be compound heterozygotes for one previously reported and one novel mutation in the gene encoding mitochondrial arginyl‐tRNA synthetase 2 ( RARS2 ). Mutations in this gene have been classically described in pontocerebellar hypoplasia type six (PCH6), a phenotype characterized by early (often intractable) seizures, profound developmental delay, and progressive pontocerebellar atrophy. The electroclinical spectrum of PCH6 is broad and includes a number of seizure types: myoclonic, generalized tonic–clonic, and focal clonic seizures. Our report expands the characterization of the PCH6 disease spectrum and presents infantile spasms as an associated electroclinical phenotype.